Influence service quality against customer loyalty : mediation role customer engagement - Agustini, Dwi Siwi; Setyawati, Harini Abrilia (Jurnal Mantik, 2025)
This study seeks to explore how service quality influences customer loyalty, with customer engagement positioned as a mediating variable. Adopting a quantitative research design, data were obtained from a survey of 105 respondents and analyzed using SmartPLS 3 with the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The findings reveal that service quality exerts a significant positive impact on both customer engagement (? = 0.527; p < 0.001) and customer loyalty (? = 0.348; p < 0.01). Additionally, customer engagement is shown to strongly predict customer loyalty (? = 0.509; p < 0.001) and serves as a pivotal mediator in the link between service quality and loyalty (? = 0.268; p < 0.001). These results suggest that, aside from improving the technical dimensions of service delivery, companies should prioritize cultivating meaningful interactions with customers to strengthen engagement, nurture emotional bonds, and secure sustainable loyalty. The findings show that service quality brings greater impact when combined with customer engagement strategies like personalization, open communication, and community-building. Managers can apply this to boost satisfaction while building loyalty that withstands competitors. This reinforces the novelty of treating engagement as the key link between service quality and long-term business success.